Effects of vasodilator and esmolol-induced hemodynamic stability on early post-operative cognitive dysfunction in elderly patients: a randomized trial - Sun, Sheng-Hui (Afr Health Sci, 2016)
OBJECTIVE: To investigate the effect of continuous intravenous injection of nicardipine and/or nitroglycerin with or without esmolol on the occurrence of early post-operative cognitive dysfunction (POCD) in elderly patients. METHODS: Elderly patients (n=340) who underwent radiofrequency ablation for atrial fibrillation were randomized into five groups: A, nicardipine; B nicardipine+esmolol; C, (nitroglycerin) group; D nitroglycerin+esmolol; E (control) groups. The hemodynamic parameters were recorded, and Mini Mental State Examination was used to assess cognitive function. RESULTS: At 30 min and 60 minutes after anesthesia and at the conclusion of surgery, the rate pressure product value was significantly lower in Groups B (10621.1±321.7, 10544.2±321.8, and 10701.3±325.5, respectively) and D (10807.4±351.1, 10784.3±360.3, and 10771.7±345.7, respectively) than in Group E (13217.1±377.6, 13203.5±357.3, and 13119.2±379.5, respectively). The heart rate was significantly higher in Groups A (104.1±10.3, 104.9±11.1, and 103.9±11.8, respectively) and C (103.7±11.3, 105.5±10.5, and 107.7±11.7, respectively) than in Group E (89.3±12.0, 88.5±11.5, and 85.5±11.6, respectively). The incidence of POCD was significantly lower in Groups A and B than in Groups C, D, and E. Univariate regression analysis showed that regimens in Groups A, B, and E and doses of propofol and fentanyl were risk factors for POCD. Multivariate logistic regression analysis revealed significant associations between the incidence of POCD and interventions in Groups A and B. CONCLUSION: Maintenance of stable intraoperative hemodynamics using nicardipine and nitroglycerin or their combinations with esmolol, especially nicardipine with esmolol, reduced the incidence of POCD in the elderly with potential cardiovascular diseases.